2019
DOI: 10.1029/2018jb016729
|View full text |Cite
|
Sign up to set email alerts
|

Posteruptive Thermoelastic Deflation of Intruded Magma in Usu Volcano, Japan, 1992–2017

Abstract: Secular ground subsidence at Usu volcano (Japan) has been reported around the eruption vents following the four eruptions in 1910, 1943, 1977, and 2000. However, the mechanisms accounting for the subsidence have not been well understood. In this study, we systematically investigated the posteruptive deformation at Usu volcano using interferometric synthetic aperture radar based on 111 JERS, ALOS-1, and ALOS-2 images acquired from 1992 to 2017. We also calculated quasi east-west and vertical ground displacement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…Studies in volcanic regions have shown that GACOS captured broad atmospheric phase delays along the coastline of Bali Island in Indonesia and reduced the variance between 35-45% in interferograms spanning Bali Island in Indonesia [49], as well as improved upon previous estimates of ground displacement velocities at Agung volcano [53]. GACOS was also shown to reduce the standard deviation by at least 20% in 45% of the interferograms spanning the Usu volcano in Japan [51]. However, application of GACOS phase delays to interferograms spanning Cerro Azul volcano in the Galapagos showed that the standard deviations of the corrected interferograms were not significantly reduced and thus were not useful for further geodetic modeling [50].…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Studies in volcanic regions have shown that GACOS captured broad atmospheric phase delays along the coastline of Bali Island in Indonesia and reduced the variance between 35-45% in interferograms spanning Bali Island in Indonesia [49], as well as improved upon previous estimates of ground displacement velocities at Agung volcano [53]. GACOS was also shown to reduce the standard deviation by at least 20% in 45% of the interferograms spanning the Usu volcano in Japan [51]. However, application of GACOS phase delays to interferograms spanning Cerro Azul volcano in the Galapagos showed that the standard deviations of the corrected interferograms were not significantly reduced and thus were not useful for further geodetic modeling [50].…”
mentioning
confidence: 81%
“…Several Remote Sens. 2020, 12, 782 3 of 30 different GWMs have been used to remove tropospheric contributions from InSAR datasets, such as the North American Regional Reanalysis (NARR) [29,31,34,35,45,46], the Modern-Era Retrospective Analysis for Research and Applications (MERRA) [29,33,39], the Moderate Resolution Imaging Spectroradiometer (MODIS) [29,38,39,43], and weather reanalysis outputs from the European Centre for Medium-Range Weather Forecasts (ECMWF): ERA40 [25,31], ERA-Interim (ERA-I) [27,29,32-34, 36,46,47], ERA5 [21,47,48], high-resolution ECMWF (hereafter HRES ECMWF) [21,29,44,[49][50][51][52][53], and operational analysis [31]. From the GWMs, tropospheric phase delay maps that incorporate estimates of both the wet and dry phase delays can be created.…”
mentioning
confidence: 99%
“…Recent space geodetic observations reveal that Showa-Shinzan has been subsiding more or less constantly with a rate of about 16 mm/yr in the last ∼25 years (Aoyama et al 2009;Wang and Aoki 2019). Wang and Aoki (2019) suggested that this subsidence is due to the thermal contraction of the emerged lava dome. Indeed, the heat brought at the time of the dome emergence has not been wholly released; the temperature of the fumarole was still 190 • C as of early 1997, decreasing from 1000 • C in 1945 and ∼500 • C in 1960 (Minakami et al 1951;Yokoyama and Seino 2000).…”
Section: Usu Volcano and The Showa-shinzan Lava Domementioning
confidence: 99%
“…The NEF of Asama volcano exhibits continuous subsidence during the whole period. Recent studies have shown that continuous subsidence at active volcanoes may be explained by several mechanisms such as magma withdrawal (e.g., Lu et al 2010), consolidation of erupted deposits (e.g., Grapenthin et al 2010), viscoelastic relaxation of the host rock (Yamasaki et al 2018), thermal contraction of lava deposits or intruded magma body (e.g., Tallarico 2003;Wang and Aoki 2019), and the pore pressure drop associated with hydrothermal fluid circulations (Wauthier et al 2018). We first excluded the magma withdrawal and viscoelastic relaxation, because these two mechanisms generally induce broadly symmetric deformation around the magma source, inconsistent with the observed deformation.…”
Section: Possible Mechanism For the Deformation At Nefmentioning
confidence: 99%
“…We thus suggest that the thermoelastic contraction of the 1783 lava flow is unlikely to fully explain the subsidence at NEF of Asama, where subsidence with rates up to − 10 mm/year is observed. Moreover, considering that meteorological precipitation and groundwater flow would accelerate the cooling process (Chaussard 2016;Wang and Aoki 2019), some other mechanism must also contribute to the observed subsidence at NEF of Asama.…”
Section: Possible Mechanism For the Deformation At Nefmentioning
confidence: 99%